Association between climate indicators and hay fever incidence in children and adolescents in Freiburg, Germany - Dao-Siebel, Trang; Holstiege, Jakob; Graw, Kathrin; Müller, Christoph; Matzarakis, Andreas; Halbleib, Roxana; Lamy, Evelyn (Frontiers in Public Health, 2025)
BackgroundAllergic conditions including hay fever are a sentinel measure of environmental impact on human health in early life. In this study we investigated the association between climate indicators and allergic rhinitis (hay fever) incidence in children and adolescents in Freiburg im Breisgau (Germany), as a representative study site for an urban German environment.MethodsData on climate indicators and hay fever incidence in children and adolescents in the period 2013 to 2021 were implemented within the free software environment for statistical computing R using generalized additive Gamma family models.ResultsOur results from all “seasonal”, “non-seasonal”, and “single-factor” models could not support the associations between the hay fever incidence and the precipitation as well as the concentrations of PM10, NO2, and O3 in Freiburg. However, they indicated statistically significant associations with temperature, and wind speed at the 5% level. The hay fever incidence was highest, as the temperature was between 4–6°C, and 10–17°C, and the wind speed was between 2.0 and 2.1m/s.ConclusionsThis knowledge could be of relevance for the choice of patient treatment procedure in Freiburg, as the symptoms of a cold or flu can easily be mistaken for an allergy, especially in the cold season.